Eucalyptus, as a Raw Material, in the Commercial Manufacture of Charcoal and Acetic Acid - Palekanda, M. W. (Indian Forester, 1958)
The merits of the cultivated Eucalyptus in the yield of charcoal and acetic acid is discussed in comparison with the yield from the conventional jungle wood of the moist deciduous belt of Mysore Forests. Experimental extraction of acetic acid was done for the first time under factory conditions at the Mysore Iron and Steel Works out of the Eucalyptus wood supplied by the Fuel Division in 1957. The results proved the superiority of Eucalyptus in the manufacture of acetic acid and charcoal over the conventional mixed jungle wood.